A performance musical do Clube do Choro da Paraíba - Bastos, Juliana Carla (2010)
Spaces known as "music’s clubs" have matured, throughout the history of Brazilian’s popular and urban music, as spaces where people meet for consideration of one or more musical genres. Inside this categorization, the "choro’s clubs", meets lovers, scholars, admirers, supporters, and since the end of the 20th century and early 21th century, choro’s researchers and / or other social and cultural phenomena involved in those contexts. The “choro’s clubs” are present in various Brazilian states, in all the regions, each one with its own peculiarities inherent to the political contexts, geographical and cultural contexts in which they are inserted. Based on this precept, I watched for almost two years, the performance of the Clube do Choro da Paraíba, seeking to identify and understand your core issues and the relationship between the speech of the authors that deal with the musical performance from the perspective of ethnomusicology and between the reports of other scholars who have observed other choro’s clubs in the Brazil. The research was based on an extensive literature, not only in ethnomusicology, but in areas related to the purpose of research, and was established in the field by means of data collection such as participant observation and interviews. At the end of the work of data analysis, it possible to see what are the main aspects that characterize the performance of the Clube do Choro da Paraíba and highlight the intense and essential interrelationship between the elements of this musical phenomenon in something at the same time, similar to other Brazilian’s choro’s clubs; and particularly as the context of performance itself.